Insight into the roles of tightly and loosely bound extracellular polymeric substances on a granular sludge in ammonium nitrogen removal. (December 2016) - Yan, Lilong; Zhang, Xiaolei; Hao, Guoxin; Guo, Yihan; Ren, Yuan; Yu, Liangbin; Bao, Xuefei; Zhang, Ying
Highlights: Ammonium, nitrite and nitrate nitrogen were present in the LBEPSs and TBEPSs. LBEPSs and TBEPSs had a greater ability to adsorb ammonium nitrogen. LBEPSs had higher adsorption (retention) of nitrite and nitrate nitrogen. LBEPSs had greater mass transfer resistance. Abstract: To explicitly understand the function of extracellular polymeric substances in the treatment of ammonium-nitrogen-rich wastewater using aerobic granular sludge, the three forms of nitrogen (ammonium, nitrite and nitrate nitrogen) contained in tightly and loosely bound extracellular polymeric substances were analyzed. The three forms of nitrogen were monitored in the tightly and loosely bound extracellular polymeric substances in aerobic granular sludge after adsorption. The ammonium nitrogen contained in the extracellular polymeric substances was distributed in both the tightly and loosely bound forms and decreased gradually as the aeration time increased. Ammonium nitrogen remained in the tightly bound extracellular polymeric substances even after aeration was complete. The nitrite and nitrate nitrogen species in the extracellular polymeric substances were mainly present in the loosely bound extracellular polymeric substances. The sources of the three nitrogen forms detected in the extracellular polymeric substances differed relative to the different nitrogen forms.